Social Sciences Education through video games: Research and experimentation of the game Assassin’s Creed Origins, for possible didactic proposal on the teaching of heritage and culture of the ancient Egypt - Quintero Mora, Domingo Luis (Clio. History and History Teaching, 2018)
Many researchers have attributed to video games a huge potential in the use of these in teaching-learning processes. This article aims to analyze through the experimentation of the game «Assassin’s Creed Origins», if it is suitable for use as a teaching resource in the teaching, including procedural aspects and attitudes related to the Social Sciences; and more specifically to the teaching and learning of different fields or social sections, such as the economy, society, management, division or recognition of the Egyptian territory. To summarize, we decide ourselves if the game is capable of transmitting or recognize in it, fundamental elements of the culture of ancient Egypt and in particular of its heritage, whose legacy has survived up to now.
Keywords: Social Sciences Education; Ancient History; Ancient Egypt; teaching-learning; videogames; teaching resource; innovation